Crianças e infâncias: concepções e práticas pedagógicas das professoras em uma escola municipal de educação infantil - Matenhauer, Alessandra Nazareno (2023)
This research had, as a general objective, the analysis of the conception of children and childhoods and the implication of the pedagogical practices of the teachers of a municipal preschool in São Paulo, located in the west zone of the city. As specific objectives, we sought to: identify the conceptions of children and childhoods of the teachers participating in this study; identify the pedagogical practices of teachers at a municipal preschool for children aged 4 to 6 years and identify whether there are contradictions between the teachers' conceptions of children and childhood and the pedagogical practices adopted. We sought to discuss the following problem situation: “How do the conceptions of children and childhoods of the teachers of a municipal preschool in São Paulo imply in their pedagogical practices?”. Observation of pedagogical practices, document analysis and semi-structured interviews were used as data collection instruments applied to 7 teachers. For the teachers' interview process, use the following questions: "What does childhood mean?", "Define what it is to be a child.", "What are the pedagogical practices used in the school where they participate?". The theoretical studies had the contribution of Corsaro (2019), Dahlberg, Moss & Pence (2019), Freire (1997), Horn & Barbosa (2008), Horn & Silveira (2022), Kramer (2001), Sarmento & Pinto (1997 ), in addition to the documents that make up the municipal teaching of the early childhood education segment in the city of São Paulo for children aged 4 to 6 years old, among them: the City Curriculum (2019), the Normative Guidance of records in early childhood education ( 2020 ), Integrative Curriculum for Children in São Paulo (2015) and Normative Guideline No. 01 (2013). Data analysis, inspired by Bardin's content analysis, was carried out in three phases: pre-analysis (investigation phase, formulation of objectives and initial contact with the proposed theme), exploration of the proposed material (phase of formulation of a priori categories) and treatment of the results (analysis phase of the obtained results). It was identified, from the obtained results that: some teachers do not distinguish the conception of children and childhoods, that is, for them the terms are identical; the lack of intentionality is present in the pedagogical work of some teachers, although prior planning of the teaching work was verified; it was noticed that there was no consensus with regard to pedagogical practices, as some practices were significant and others archaic. A collaborative training was proposed to the teachers, during PEA (Special Action Project) times. Finally, it was concluded that continuing teacher training is a crucial element for the teacher to be able to exercise reflective thinking and act significantly in favor of the educational process